2018
DOI: 10.1002/smll.201703736
|View full text |Cite
|
Sign up to set email alerts
|

Hollow PtPdRh Nanocubes with Enhanced Catalytic Activities for In Vivo Clearance of Radiation‐Induced ROS via Surface‐Mediated Bond Breaking

Abstract: Catalytic nanomaterials can be used extrinsically to combat diseases associated with a surplus of reactive oxygen species (ROS). Rational design of surface morphologies and appropriate doping can substantially improve the catalytic performances. In this work, a class of hollow polyvinyl pyrrolidone-protected PtPdRh nanocubes with enhanced catalytic activities for in vivo free radical scavenging is proposed. Compared with Pt and PtPd counterparts, ternary PtPdRh nanocubes show remarkable catalytic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 69 publications
(97 reference statements)
2
37
0
Order By: Relevance
“…The catalytic reaction rate was concentration-dependent from 0.05 to 5 mg/mL within 70 min. The results are in agreement with previous work that ternary alloy showed superior catalytic property to H 2 O 2 than Pt, and PtPd (Wang J. Y. et al, 2018).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The catalytic reaction rate was concentration-dependent from 0.05 to 5 mg/mL within 70 min. The results are in agreement with previous work that ternary alloy showed superior catalytic property to H 2 O 2 than Pt, and PtPd (Wang J. Y. et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Our previous work showed that PtPd nanocubes decreased the ROS level by 14.8% after 4Gy radiation (Long et al, 2019). Besides, PtPdRh nanocubes can reduce radiation-induced ROS by 18.8% (Wang J. Y. et al, 2018). However, the present PtPdMo nanocubes exhibited superior ROS scavenge ability (35.5%) via doping induced surface defect, therefore prevented ROS damages to cells and increased the survival rate after radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation damage is closely related to free radical release [1921]. Studies have shown that chronic administration of the SOD mimic AEOL-10150 has a protective effect on radiation-induced lung injury, whereas low-dose or short-term AEOL-10150 treatment has no effect on radiation-induced lung injury [22, 23].…”
Section: Introductionmentioning
confidence: 99%